Phase I trial outcome of amnion cell therapy in patients with ischemic stroke (I-ACT) - Phan, Thanh G.; Lim, Rebecca; Chan, Siow T.; McDonald, Hannah; Gan, Poh-Yi; Zhang, Shenpeng R.; Barreto Arce, Liz J.; Vuong, Jason; Thirugnanachandran, Tharani; Clissold, Benjamin; Ly, John; Singhal, Shaloo; et al. (Frontiers in Neuroscience, 2023)
Background: We proposed a Phase I dose escalation trial to assess the safety of allogeneic human amniotic epithelial cells (hAECs) in stroke patients with a view to informing the design for a Phase II trial. Methods: The design is based on 3+3 dose escalation design with additional components for measuring MR signal of efficacy as well as the effect of hAECs (2 to 8x106/kg, i.v.) on preventing immunosuppression after stroke. Results: Eight patients (6 males) were recruited within 24 h of ischemic stroke onset and were infused with hAECs. We were able to increase the dose of hAECs to 8x106 cells/kg (2x106/kg, n=3; 4x106/kg, n=3; 8x106/kg, n=2). The mean age is 68.0±10.9 (mean±SD). The frequencies of hypertension and hyperlipidemia were 87.5%, diabetes was 37.5%, atrial fibrillation was 50%, ischemic heart disease was 37.5% and ever-smoker was 25%. Overall, baseline NIHSS was 7.5±3.1, 7.8±7.2 at 24 h, and 4.9±5.4 at 1 week (n=8). The modified Rankin scale at 90 days was 2.1±1.2. Supplemental oxygen was given in 5 patients during hAEC infusion. Using predefined criteria, two serious adverse events occurred. One patient developed recurrent stroke and another developed pulmonary embolism whilst in rehabilitation. For the last 4 patients, infusion of hAECs was split across separate infusions on subsequent days to reduce the risk for fluid overload. Conclusion: Our Phase I trial demonstrates that a maximal dose of 2x106/kg hAECs given intravenously each day over 2 days (a total of 4x106/kg) is safe and optimal for use in a Phase II trial.